Metacognitive Therapy for Social Anxiety Disorder: An A–B Replication Series Across Social Anxiety Subtypes - Nordahl, Henrik; Wells, Adrian (Frontiers in Psychology, 2018)
Cognitive behavioral therapy (CBT) is the treatment of choice for Social anxiety disorder (SAD). However, factors additional to those emphasized in CBT are the primary cause of psychological disorder according to the metacognitive model. Metacognitive Therapy (MCT) aims to target a perseverative thinking style named the cognitive attentional syndrome and its underlying metacognitive beliefs (beliefs about cognition). The present study aimed to explore the effects of generic MCT for SAD. Treatment related effects were evaluated using direct replication single case (A-B) methodology across 3 patients with different subtypes of SAD; performance type, generalized and generalized plus avoidant personality disorder, representing increasing SAD severity/complexity. All patients responded during treatment and achieved substantial symptom reductions which were largely maintained at 6 months’ follow-up. Metacognitive therapy appears to be a suitable treatment and was associated with positive outcomes for patients with different presentations of SAD.